Belosnezhka i sem' gnomov . Belosnezhka i sem' gnomov . Snow White and the Seven Dwarfs . Белоснежка и семь гномов - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the journalist Leonid Parfenov about his career and personal life. Featured in the program: Parfenov, Leonid Gennadievich (Journalist) Contributors: Riazanov, El'dar (Anchor) Интервью с журналистом Леонидом Парфеновым о его карьере и личной жизни. В программе участвуют: Парфенов, Леонид Геннадиевич (Журналист) Создатели: Рязанов, Эльдар (Ведущий/Ведущая)